Adamantane‐Substituted Acridine Donor for Blue Dual Fluorescence and Efficient Organic Light‐Emitting Diodes. (12th December 2018) - Li, Wei; Cai, Xinyi; Li, Binbin; Gan, Lin; He, Yanmei; Liu, Kunkun; Chen, Dongcheng; Wu, Yuan‐Chun; Su, Shi‐Jian
Abstract: To date, blue dual fluorescence emission (DFE) has not been realized because of the limited choice of chemical moieties and severe geometric deformation of the DFE emitters leading to strong intramolecular charge transfer (ICT) with a large Stokes shift in excited states. Herein, an emitter (1′r, 5′ R, 7′ S )‐10‐(4‐(4, 6‐diphenyl‐1, 3, 5‐triazin‐2‐yl)phenyl)‐10H‐spiro [acridine‐9, 2′‐adamantane] (a‐DMAc‐TRZ) containing a novel adamantane‐substituted acridine donor is reported, which exhibits unusual blue DFE. The introduction of the rigid and bulky adamantane moiety not only suppressed the geometry relaxation in excited state, but also induced the formation of quasi‐axial conformer (QAC) and quasi‐equatorial conformer (QEC) geometries, leading to deep‐blue conventional fluorescence and sky‐blue thermally activated delayed fluorescence (TADF). The resulting organic light‐emitting diodes (OLEDs) achieved a maximum external quantum efficiency (EQE) of about 29 %, which is the highest reported for OLEDs based on dual‐conformation emitters.